Brief study of the recitation of The Holy Quran (Salam International Academic Journal, 2019)
Brief study of the recitation of The Holy QuranHoly Quran is Allah’s last book which was descended to Prophet Mohammed (PBUH), Allah has granted Muslim Ummah with tremendous blessings, Quran is the greatest among all these blessings.The Holy book (Quran) is descended for the sake of guidance and instruction not only for Muslim, but also for the entire humanity as Allah says “That this tremendous book is a complete code of life for rehabilitation, framework and instructions of living because without it spending a successful life would be impossible.History has witnessed that when the Muslim Ummah accepted this book (Quran), made it real aims of their lives so Allah granted them a life with integrity and honor because of this sacred book (Quran). Earth and Skies opened their treasures for them and wished them success in every span of life. They were knowledge blessed in entire human beings. They were called leader and an example of moral and good manner.  Poverty and drought got rid of them so if we want to be blessed with divinely honor and improvement, as Muslim Ummah we should get rid of problems and disasters and be blessed with high ranks, welfare, safety and peace so then we are bound to refer back to Quran with Open heart and support this book as our ancestors did.One of the areas that our ancestors had believed in they are Quranic Verses and they have written numerous books on it. Numerous scholars and Quran readers devoted their life for getting this valued knowledge. It has been tried to discuss different facts of Quranic Verses in the given topics.·        Definition of recitation (Reading) and its explanation·        Different proved reasons of recitation (Reading)·        Types of recitation (Reading)·        Bets for verses acceptance ·        Benefits and advantages of the recitation (Reading)